The Effort To Increase Brand Loyalty For Es Teh Indonesia: - - Damis Veri Budianto; Sudarmiatin (Cita konsultindo, 2024)
Brand loyalty includes emotional and rational aspects, where consumers feel an emotional connection and believe that the brand provides the best value. This research investigates the influence of brand image and brand trust on brand loyalty and brand satisfaction by considering brand satisfaction as an intervening variable for the beauty of Indonesian products. The main objective of this research is to analyze the causal relationship between the independent variable and the dependent variable with the presence of an intermediary variable. The main data source for this research is Esteh Indonesia customers. Data was collected from a total of 208 customers throughout Indonesia who are fans of Esteh Indonesia. Meanwhile, the research methodology uses a purposive sampling method and the PLS 3.0 testing tool is used for statistical analysis. The majority of Esteh Indonesia customers in the sample were women (57.2%), aged between 26-35 years (43.3%), had secondary/equivalent education (41.3%), and had a bachelor's degree (49%). Last month, once or twice. The results of this research are as follows: First, brand image only makes a small contribution to brand loyalty. Second, brand image contributes to brand satisfaction. Third, brand satisfaction contributes significantly to brand loyalty. Fourth, brand trust contributes significantly to brand loyalty. Fifth, brand trust contributes significantly to brand satisfaction. Sixth, brand image contributes significantly to brand loyalty through brand satisfaction. Seventh, brand trust contributes significantly to brand loyalty through brand satisfaction.